Understanding consumer behavior in choosing bear brand milk products using the Analytical Hierarchy Process (AHP) method - Prabantoro, Gatot; Amanah, Aam; Megayani, Megayani; Mulyati, Ade (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2024)
This research aims to understand the behavior of consumers of BB milk products using the Analytic Hierarchy Process (AHP) method. This research uses a qualitative method with analysis using the AHP method to help determine consumer choices in choosing the BB milk products they consume by considering price, promotion, packaging, location, and product benefits. Data and information were collected through in-depth interviews with 21 informants who were consumers who frequently consumed BB milk products, then the data and information were converted into questionnaire answers and processed using the AHP method. The research results show that consumers mostly consider product benefits and strong promotions as the basis for decisions before purchasing BB milk products. The most frequently purchased product variant is BB Original.